2021
DOI: 10.1111/1460-6984.12649
|View full text |Cite
|
Sign up to set email alerts
|

Making the case for the collection of a minimal dataset for children with speech sound disorder

Abstract: Background: NHS case note data is a potential source of practice-based evidence which could be used to investigate effectiveness of different interventions for individuals with a range of speech, language and communication needs. Consistency in pre-and post-intervention data as well as collection of relevant variables would need to be demonstrated as a precursor to adopting this approach in future investigations of SLT intervention.Aims: The aim of this paper is to explore whether routine clinical data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Surrounding literature provides support with some authors suggesting this is an efficient method for obtaining a spontaneous, connected speech sample within a limited time frame (Bleile, 2002) . The lack of standardised assessments to assess children with suspected SSD has also been reported as a challenge in many other countries where the profession of speech and language therapy is relatively new (Joginder Singh et al, 2016) as well as in some English-speaking countries (Morgan et al, 2021) and the Sri Lankan participants in this study reported similar challenges accordingly. The participant interviews noted a lack of standardised assessments affecting the ability to make accurate clinical diagnoses around the nature of a child's SSD, which may lead to inaccurate diagnoses.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Surrounding literature provides support with some authors suggesting this is an efficient method for obtaining a spontaneous, connected speech sample within a limited time frame (Bleile, 2002) . The lack of standardised assessments to assess children with suspected SSD has also been reported as a challenge in many other countries where the profession of speech and language therapy is relatively new (Joginder Singh et al, 2016) as well as in some English-speaking countries (Morgan et al, 2021) and the Sri Lankan participants in this study reported similar challenges accordingly. The participant interviews noted a lack of standardised assessments affecting the ability to make accurate clinical diagnoses around the nature of a child's SSD, which may lead to inaccurate diagnoses.…”
Section: Discussionmentioning
confidence: 79%
“…More than 50% of American SLTs (Skahan et al., 2007) always use the Goldman‐Fristoe Test of Articulation and 84% of SLTs in the UK used the South Tyneside Assessment of Phonology (Joffe & Pring, 2008). However, another study in the UK reported 52.3% of SLTs used in‐house designed, informal picture naming assessments (Morgan et al., 2021). In addition to single word picture naming tests, more Australian SLTs (58.3%) reported using conversational speech samples always in assessment in comparison to SLTs from the US (36.2%) to complement their findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, prior to implementation of the QI project, different formal and informal speech assessments were used pre- and post-intervention per child precluding calculation of PCCs across the baseline period because of the lack of comparability between the speech data targeted. 35 …”
Section: Resultsmentioning
confidence: 99%
“…However, a review of existing case notes of children treated for SSD were found to be too incomplete to compare Open access pathways. 11 Additionally, it was found that preintervention and postintervention data and variables recorded in the clinical case notes varied significantly between and within SLT services, thereby negating comparison. As a first step to determining which care pathways are most effective and efficient, this umbrella review will ask which assessment and outcome measures are commonly employed with children with SSD.…”
Section: Implications For Clinical Practicementioning
confidence: 99%